Hybrid electrolyte and preparation method and application thereof

By using the coordination between naphthoquinone compounds and zinc ions in zinc ion mixing capacitors, a hybrid electrolyte was constructed, which solved the problem of insufficient stability of zinc negative electrodes, improved electrochemical performance and reduced costs, and achieved a safe and reliable high-performance capacitor.

CN119673679APending Publication Date: 2025-03-21SUN YAT SEN UNIV
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411560738.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-04
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

The existing zinc ion hybrid capacitors have insufficient stability in the zinc negative electrode in the aqueous electrolyte, which leads to dendrite growth and corrosion problems, limiting their practical application. At the same time, traditional organic ester electrolyte additives are costly and have safety hazards.

Method used

Naphthoquinone compounds are used as components of the hybrid electrolyte, combined with soluble zinc salt and water, and the electrode stability is optimized through the coordination between naphthoquinone compounds and zinc ions, and the high-efficiency conversion of electrical energy and chemical energy is promoted through its good reversibility.

Benefits of technology

It significantly improves the electrochemical performance of zinc ion hybrid capacitors, reduces polarization voltage, extends service life, and reduces production costs and avoids safety hazards.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119673679A_ABST
    Figure CN119673679A_ABST
Patent Text Reader

Abstract

The invention discloses a hybrid electrolyte as well as a preparation method and application thereof. The hybrid electrolyte comprises a naphthoquinone compound, soluble zinc salt and water. The naphthoquinone compound is used as a component of the hybrid electrolyte to construct the redox electrolyte, and compared with a traditional electrolyte based on electrolyte salt and an organic solvent, coordination with zinc ions can be achieved, the electrode stability is improved, and efficient conversion between electric energy and chemical energy is promoted. The electrolyte with naphthoquinone substances as additives is used for preparing a capacitor or a battery, the naphthoquinone substances effectively guide uniform deposition of zinc ions by optimizing charge distribution and improving a nucleation phenomenon at an interface of an electrode and the electrolyte, and the uniform deposition is beneficial to reducing polarization voltage and preventing zinc dendrites from being formed, so that the performance of the capacitor or the battery is improved, and the service life of the capacitor or the battery is prolonged. And the reversible oxidation-reduction reaction is carried out in the charging and discharging process of the capacitor, so that the performance of the battery and the capacitor is greatly improved, and the method has remarkable significance in improving the overall stability of the zinc ion battery or the capacitor and promoting commercialization.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of electrochemistry, and in particular relates to a hybrid electrolyte and a preparation method and application thereof. Background Art

[0002] At present, the demand for efficient and reliable electrochemical energy storage systems continues to rise. Among the many energy storage options, lithium-ion batteries have won the market dominance with their superior energy and power density. However, due to the scarcity of lithium resources, high costs, safety hazards and other issues, its development faces restrictions. Therefore, the research of non-lithium-based energy storage systems has become urgent. In recent years, due to the rich zinc resources, low cost, environmental friendliness and easy processing, aqueous zinc ion energy storage systems have become a new focus of power storage systems. Among them, zinc ion hybrid capacitors have both the high energy density of battery energy storage devices and the high power density of supercapacitor energy storage devices, showing strong application potential. However, the stability of zinc negative electrodes in aqueous electrolytes is insufficient, especially the problems of dendrite growth and corrosion, which limit their practical application. In response to this problem, researchers have conducted a lot of research work, and improved electrolytes have been proven to be a simple and effective solution. Among them, organic small molecule additives are safe and non-toxic, and have significant performance improvement effects, and have become a research hotspot in recent years.

[0003] Currently, the commonly used electrolyte additives are mainly organic ester electrolyte additives, which can selectively adsorb on the zinc deposition site, induce uniform distribution of ion concentration and electric field near the zinc negative electrode, and then improve the interface environment between the zinc negative electrode and the electrolyte, avoid excessive growth of zinc dendrites, and reduce corrosion and passivation of the zinc negative electrode. However, traditional organic ester electrolyte additives are expensive and have safety hazards such as flammability and toxicity, which limits their practical application in the field of large-scale energy storage.

[0004] At the same time, it has been found that most additives, including organic molecules and ionic compounds, have single functions, high costs or poor environmental friendliness. Most researchers have conducted research on adding multiple additives to the same electrolyte (such as a first additive and a second additive system). However, this method will increase the production cost of electrochemical devices and the process is complicated. Therefore, the importance of developing multifunctional electrolyte additives for the construction of high-performance aqueous zinc ion hybrid capacitors has gradually become prominent. Summary of the invention

[0005] In order to overcome the problems existing in the above-mentioned prior art, one of the purposes of the present invention is to provide a hybrid electrolyte. The second purpose of the present invention is to provide a method for preparing the above-mentioned hybrid electrolyte. The third purpose of the present invention is to provide an application of the above-mentioned hybrid electrolyte. The fourth purpose of the present invention is to provide a hybrid capacitor.

[0006] Redox electrolyte is a special type of electrolyte that greatly improves the performance of traditional electrolytes based on electrolyte salts and organic solvents by integrating reversible redox reaction substances. This innovation not only enhances the energy density, power density and cycle life of energy storage devices, but also achieves efficient conversion between electrical energy and chemical energy by introducing electrochemically active substances, optimizing the performance of secondary batteries and supercapacitors. The present invention uses naphthoquinone compounds as components of hybrid electrolytes. Naphthoquinone compounds and their derivatives have a variety of polar groups that can coordinate with zinc ions and improve electrode stability. At the same time, their "naphthoquinone" groups often have good reversibility during the device charging and discharging process. The reversible process is more stable than molecules such as phenol. Therefore, the use of naphthoquinone compounds as additives in electrolytes provides new possibilities for the design of energy storage devices.

[0007] In order to achieve the above object, the technical solution adopted by the present invention is:

[0008] A first aspect of the present invention provides a hybrid electrolyte, characterized in that it comprises a naphthoquinone compound, a soluble zinc salt and water.

[0009] Preferably, the main components of the hybrid electrolyte are water and a soluble zinc salt, with naphthoquinone compounds as additives.

[0010] Preferably, the concentration of the naphthoquinone compound in the hybrid electrolyte is 0.01-1000 mmol·L -1 .

[0011] More preferably, the concentration of the naphthoquinone compound in the hybrid electrolyte is 0.1-50 mmol·L -1 .

[0012] Further preferably, the concentration of the naphthoquinone compound in the hybrid electrolyte is 0.05-10 mmol·L -1 .

[0013] Preferably, the naphthoquinone compound is selected from substituted or unsubstituted 1,4-naphthoquinone, substituted or unsubstituted 1,2-naphthoquinone and corresponding salts or derivatives; the substituents of the substituted 1,4-naphthoquinone and substituted 1,2-naphthoquinone are independently selected from hydroxyl, halogen, methyl, nitro and sulfonic acid.

[0014] The term "salt" refers to salts of the compounds of the present invention, prepared from the compounds having specific substituents discovered in the present invention and relatively non-toxic acids or bases. Electrochemically acceptable salts are preferred.

[0015] More preferably, the naphthoquinone compound includes at least one of 1,2-naphthoquinone, sodium 1,2-naphthoquinone-4-sulfonate, 1,4-naphthoquinone, 2,3-dichloro-5-nitro-1,4-naphthoquinone, 2-hydroxy-1,4-naphthoquinone, sodium menadione bisulfite, 2,3-dichloro-1,4-naphthoquinone, and 5,8-dihydroxy-1,4-naphthoquinone.

[0016] Preferably, the soluble zinc salt is selected from at least one of zinc trifluoromethanesulfonate, zinc bistrifluoromethanesulfonate imide, zinc perchlorate, zinc sulfate, zinc chloride, zinc nitrate, zinc acetate, zinc fluoride, zinc hexafluoride, zinc tetrafluoroborate and zinc gluconate.

[0017] Preferably, the concentration of the soluble electrolyte in the hybrid electrolyte is 0.1-10 mol·L -1 .

[0018] More preferably, the concentration of the soluble electrolyte in the hybrid electrolyte is 1-5 mol·L -1 .

[0019] Preferably, the hybrid electrolyte further includes at least one of potassium salt, sodium salt, ammonium salt and nitrate.

[0020] The second aspect of the present invention provides a method for preparing the aqueous electrolyte described in the first aspect, comprising the following steps: mixing a naphthoquinone compound, a soluble zinc salt and water to prepare a hybrid electrolyte.

[0021] The third aspect of the present invention provides use of the hybrid electrolyte described in the first aspect in preparing a capacitor or a battery.

[0022] Preferably, the hybrid electrolyte is used in the preparation of supercapacitors, hybrid capacitors or metal ion batteries.

[0023] A fourth aspect of the present invention provides a hybrid capacitor comprising a positive electrode, a negative electrode and the hybrid electrolyte described in the first aspect.

[0024] Preferably, the positive electrode is a positive electrode current collector loaded or unloaded with a positive electrode active material; the positive electrode active material is selected from at least one of activated carbon, carbon nanotubes, MXene, manganese-based oxides, vanadium-based oxides, Prussian blue derivatives, polyanion compounds, and organic positive electrode materials.

[0025] Preferably, the negative electrode is metallic zinc or a metal modified with metallic zinc.

[0026] Preferably, the operating current range of the hybrid electrolyte is 0.01-50 mA cm -2 .

[0027] The beneficial effects of the present invention are:

[0028] The present invention discloses a hybrid electrolyte, in which naphthoquinone compounds are used as components of the hybrid electrolyte to construct a redox electrolyte. Compared with the traditional electrolyte based on electrolyte salts and organic solvents, the hybrid electrolyte can achieve coordination with zinc ions, improve electrode stability, promote efficient conversion between electrical energy and chemical energy, and thus greatly improve the performance of batteries and capacitors. At the same time, naphthoquinone compounds often have good reversibility during the charge and discharge process of the device, and the reversible process is more stable than that of molecules such as phenol. Therefore, the application of naphthoquinone compounds as additives in electrolytes provides new possibilities for the design of energy storage devices.

[0029] Specifically, compared with the prior art, the present invention has the following advantages:

[0030] 1. The present invention provides an electrolyte with naphthoquinone substances as additives and the application of preparing capacitors or batteries. The naphthoquinone substances effectively guide the uniform deposition of zinc ions by optimizing the charge distribution and improving the nucleation phenomenon at the interface between the electrode and the electrolyte. This uniform deposition helps to reduce the polarization voltage and prevent the formation of zinc dendrites, and reversible redox reactions are carried out during the charging and discharging process of the capacitor, thereby significantly improving the electrochemical performance of the zinc ion hybrid capacitor. In addition, the electrolyte preparation process proposed by the present invention is simple and low in cost, which is of great significance for improving the overall stability of zinc ion batteries or capacitors and promoting their commercialization.

[0031] 2. The electrolyte additive described in the present invention can be adsorbed on the surface of the zinc metal negative electrode, by reshaping the charge distribution and nucleation characteristics of the electrode and electrolyte interface, and forming hydrogen bonds with water molecules to reduce their activity, thereby effectively inhibiting the generation of hydrogen. This mechanism of action not only promotes the uniform deposition of zinc ions and avoids the formation of zinc dendrites, but also significantly reduces the polarization voltage and prolongs the service life of the aqueous zinc ion hybrid capacitor. The aqueous zinc ion hybrid capacitor involved in the present invention uses an electrolyte additive containing specific functional groups such as sulfonate, hydroxyl, nitro, and ketocarbonyl, and regulates the deposition behavior of zinc through simple processes and low-cost raw materials, effectively inhibiting the formation of zinc dendrites and improving the cycle life of the battery. Combined with the use of high-capacity positive electrode materials, the energy density, cycle life and safety of aqueous zinc ion batteries / capacitors can be further improved, and its industrialization process can be promoted. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 are photos of aqueous additive solutions and hybrid electrolytes;

[0033] Figure 2 UV-visible absorption spectra analysis of aqueous solutions and hybrid aqueous solutions of additives in Examples 3, 5, and 7;

[0034] Figure 3The cycle performance test results of the symmetrical batteries of Examples 1-8 and Comparative Example 1;

[0035] Figure 4 The anode scanning electron microscope images of the aqueous zinc ion symmetric battery prepared in Example 5, Example 8 and Comparative Example 1;

[0036] Figure 5 CV test graphs of the hybrid capacitors of Example 4 and Comparative Example 1;

[0037] Figure 6 Schematic diagram of the "electrode-electrolyte" interface reaction in the traditional electrolyte prepared in Comparative Example 1;

[0038] Figure 7 Schematic diagram of the redox "electrode-electrolyte" interface reaction prepared in Examples 1-8. DETAILED DESCRIPTION

[0039] The present invention is further described in detail below through specific examples. The raw materials used in the following examples, unless otherwise specified, can be obtained from conventional commercial sources or prepared and separated by simple synthesis; the processes used, unless otherwise specified, are conventional processes in the art.

[0040] The naphthoquinone compounds described in the following examples are representative electrolyte additives. Their specific Chinese and English names, English abbreviations, chemical structural formulas, suppliers and CAS numbers are shown in Table 1:

[0041] Table 1

[0042]

[0043]

[0044] Example 1

[0045] This embodiment provides a hybrid electrolyte and a symmetrical battery and a hybrid capacitor, and the specific preparation method is as follows:

[0046] 1. Preparation of hybrid electrolyte

[0047] At room temperature, 28753.00 mg of zinc sulfate heptahydrate was completely dissolved in 50 mL of deionized water, and then 39.50 mg of 1,2-naphthoquinone (ONQ, 5 mmol·L -1 ), mix well and set aside.

[0048] 2. Preparation of symmetric batteries and hybrid capacitors

[0049] Zinc foil is used as the negative electrode and filter paper is used as the diaphragm to assemble the Zn / / Zn symmetric battery and zinc ion hybrid capacitor. The preparation process of positive and negative electrodes: the surface of the zinc foil is polished with sandpaper, and then cut into discs with a diameter of 11.3 mm, ultrasonically cleaned with ethanol, placed in an oven for drying, and taken out for use. The positive electrode uses activated carbon as the positive electrode material.

[0050] Assemble button-type LIR2032 symmetrical battery and hybrid capacitor: First, put the spring into the negative electrode shell, then put in the diaphragm, drip the electrolyte to wet the diaphragm, then put in the zinc sheet (symmetrical battery) or positive electrode sheet (hybrid capacitor), gasket, washer and positive electrode shell in turn, and then put it into the static press for static pressure sealing, and put the assembled battery into a vacuum drying oven (25℃) for 4 hours for standby use. Then use the assembled symmetrical battery and zinc ion hybrid capacitor for cycle performance testing.

[0051] Example 2

[0052] This embodiment provides a hybrid electrolyte and a symmetrical battery and a hybrid capacitor, and the specific preparation method is as follows:

[0053] 1. Preparation of hybrid electrolyte

[0054] At room temperature, 28753.00 mg of zinc sulfate heptahydrate was completely dissolved in 50 mL of deionized water, and then 68.00 mg of 2,3-dichloro-5-nitro-1,4-naphthoquinone (CNNQ, 5 mmol / L) was added. -1 ), mix well and set aside.

[0055] 2. The preparation method of the symmetrical battery and the hybrid capacitor is the same as that of Example 1.

[0056] Example 3

[0057] This embodiment provides a hybrid electrolyte and a symmetrical battery and a hybrid capacitor, and the specific preparation method is as follows:

[0058] 1. Preparation of hybrid electrolyte

[0059] At room temperature, 28753.00 mg of zinc sulfate heptahydrate was completely dissolved in 50 mL of deionized water, and then 43.50 mg of 2-hydroxy-1,4-naphthoquinone (HNQ, 5 mmol·L -1 ), mix well and set aside.

[0060] 2. The preparation method of the symmetrical battery and the hybrid capacitor is the same as that of Example 1.

[0061] Example 4

[0062] This embodiment provides a hybrid electrolyte and a symmetrical battery and a hybrid capacitor, and the specific preparation method is as follows:

[0063] 1. Preparation of hybrid electrolyte

[0064] At room temperature, 28753.00 mg of zinc sulfate heptahydrate was completely dissolved in 50 mL of deionized water, and then 69.10 mg of sodium menadione bisulfite (MNQS, 5 mmol / L) was added. -1 ), mix well and set aside.

[0065] 2. The preparation method of the symmetrical battery and the hybrid capacitor is the same as that of Example 1.

[0066] Example 5

[0067] This embodiment provides a hybrid electrolyte and a symmetrical battery and a hybrid capacitor, and the specific preparation method is as follows:

[0068] 1. Preparation of hybrid electrolyte

[0069] At room temperature, 28753.00 mg of zinc sulfate heptahydrate was completely dissolved in 50 mL of deionized water, and then 39.50 mg of 1,4-naphthoquinone (PNQ, 5 mmol·L -1 ), mix well and set aside.

[0070] 2. The preparation method of the symmetrical battery and the hybrid capacitor is the same as that of Example 1.

[0071] Example 6

[0072] This embodiment provides a hybrid electrolyte and a symmetrical battery and a hybrid capacitor, and the specific preparation method is as follows:

[0073] 1. Preparation of hybrid electrolyte

[0074] At room temperature, 28753.00 mg of zinc sulfate heptahydrate was completely dissolved in 50 mL of deionized water, and then 56.75 mg of 2,3-dichloro-1,4-naphthoquinone (CNQ, 5 mmol·L -1 ), mix well and set aside.

[0075] 2. The preparation method of the symmetrical battery and the hybrid capacitor is the same as that of Example 1.

[0076] Example 7

[0077] This embodiment provides a hybrid electrolyte and a symmetrical battery and a hybrid capacitor, and the specific preparation method is as follows:

[0078] 1. Preparation of hybrid electrolyte

[0079] At room temperature, 28753.00 mg of zinc sulfate heptahydrate was completely dissolved in 50 mL of deionized water, and then 65.00 mg of 1,2-naphthoquinone-4-sulfonate sodium (NQS, 5 mmol·L-1 ), mix well and set aside.

[0080] 2. The preparation method of the symmetrical battery and the hybrid capacitor is the same as that of Example 1.

[0081] Example 8

[0082] This embodiment provides a hybrid electrolyte and a symmetrical battery and a hybrid capacitor, and the specific preparation method is as follows:

[0083] 1. Preparation of hybrid electrolyte

[0084] At room temperature, 28753.00 mg of zinc sulfate heptahydrate was completely dissolved in 50 mL of deionized water, and then 69.10 mg of 5,8-dihydroxy-1,4-naphthoquinone (NQH, 5 mmol·L -1 ), mix well and set aside.

[0085] 2. The preparation method of the symmetrical battery and the hybrid capacitor is the same as that of Example 1.

[0086] Comparative Example 1

[0087] This comparative example provides an electrolyte and a symmetrical battery and a hybrid capacitor, and the specific preparation method is as follows:

[0088] 1. Preparation of electrolyte

[0089] At room temperature, 28753.00 mg of zinc sulfate heptahydrate was completely dissolved in 50 mL of deionized water for later use.

[0090] 2. The preparation method of the symmetrical battery and the hybrid capacitor is the same as that of Example 1.

[0091] Experimental analysis

[0092] 1. Comparison between additive aqueous solution and hybrid electrolyte

[0093] The naphthoquinone compounds described in Examples 1-8 are configured as additive aqueous solutions, and compared with the hybrid aqueous solutions of Examples 1-8 without electrolyte, the additive aqueous solutions and the hybrid electrolytes are compared. Figure 1 As shown, the MNQS aqueous solution is white in color, and changes color after mixing with the zinc sulfate solution, which indicates that MNQS interacts with the ions in the electrolyte; the PNQ aqueous solution is brown in color, and changes color after mixing with the zinc sulfate aqueous solution, which indicates that PNQ interacts with the ions in the electrolyte; the naphthoquinone compounds described in the remaining embodiments all change color after mixing with the zinc sulfate aqueous solution, which indicates that the naphthoquinone compounds described in Examples 1-8 chelate with the zinc ions in the electrolyte.

[0094] The additive aqueous solutions of Examples 3, 5, and 7 and the hybrid aqueous solution (zinc sulfate aq.) were subjected to UV-visible absorption spectroscopy analysis, and the results were as follows: Figure 2 As shown, the HNQ additive of Example 3 has absorption peaks in the two intervals of 200-300nm and 300-350nm, and the applied electric field causes the structural transformation of the HNQ additive, causing the absorption peak intensity of the 300-350 band to weaken, and the redox electrolyte shows obvious color changes under the action of the electric field; the PNQ additive of Example 5 has absorption peaks in the two intervals of 200-300nm and 300-350nm, and the applied electric field causes the structural transformation of the PNQ additive, causing the absorption peak intensity of the 300-350 band to weaken, and the redox electrolyte shows obvious color changes under the action of the electric field; the NQS additive of Example 7 has absorption peaks in the two intervals of 200-300nm and 300-400nm, and the applied electric field causes the structural transformation of the NQS additive, causing the absorption peak intensity of the 300-400 band to weaken, and the redox electrolyte shows obvious color changes under the action of the electric field.

[0095] 2. Electrochemical characterization

[0096] (1) At 25°C, 2 mA cm -2 、1mAh·cm -2 Under the electrochemical conditions of , the symmetrical batteries of Examples 1-8 and Comparative Example 1 were subjected to constant current charge and discharge tests. The cycle performance results are shown in Figure 3 As shown, the symmetrical battery using the electrolyte of Comparative Example 1 (without additives) has a short circuit phenomenon after 50 hours of circulation, and the polarization voltage is 253mV; the symmetrical batteries of Examples 1-8 show stable circulation, among which the symmetrical battery of Example 3 (HNQ) has a cycle life of more than 500 hours and a polarization voltage of 110mV; the symmetrical battery of Example 4 (MNQS) has a cycle life of more than 660 hours and a polarization voltage of 114mV; the symmetrical battery of Example 5 (PNQ) has a cycle life of more than 1400 hours and a polarization voltage of 118mV; Example 7 (NQS) The symmetrical battery cycle life of Example 8 (NQH) exceeds 120h, and the polarization voltage is 64mV; the symmetrical battery of Example 8 (NQH) exceeds 1200h, and the polarization voltage is 102mV; the symmetrical batteries of Examples 3, 4, 5 and 8 show a larger polarization voltage, which is beneficial to reduce the nucleation barrier, refine the grains, ensure the uniform distribution of current in space, and are beneficial to uniform nucleation and promote high-power energy storage, while the symmetrical battery of Example 7 shows a smaller polarization voltage, indicating that its electrochemical impedance is relatively large, which may be caused by the charge transfer and ion transfer at the "electrode-electrolyte" interface. In summary, the cycle life of the symmetrical batteries of Examples 1-8 is much greater than that of the symmetrical batteries without additives, indicating that the use of naphthoquinone compound additives can greatly improve the cycle stability of the zinc negative electrode.

[0097] At 2 mA cm 2 , 1mA·h·cm -2 The symmetrical battery of Example 5 (PNQ), the symmetrical battery of Example 8 (NQH), and the symmetrical battery of Comparative Example 1 (without additive) were cycled for 50 hours under the same conditions to obtain scanning samples. The scanning electron microscope (SEM) test results of each battery are shown in FIG. Figure 5 As shown, it can be observed that the structures of the scanned samples of Example 5 (PNQ) and Example 8 (NQH) are loose lamellar crystals, and the number of dendrites is reduced compared with the control example, while the scanned sample of Comparative Example 1 is observed to have rampant dendrite growth, and its structure is loose lamellar crystals.

[0098] (2) Cyclic voltammetry (CV) tests were performed on the hybrid capacitors of Example 4 (MNQS) and Comparative Example 1 (without additives). The CV test results are as follows: Figure 4 As shown, the CV curve of the hybrid capacitor of comparative example 1 (without additives) is quasi-rectangular, which is a typical feature of hybrid ion capacitors and has no additional capacity contribution; the CV curve of the aqueous zinc ion hybrid capacitor of Example 4 with the addition of MNQS has a significant prominent peak, indicating that additional capacity is added.

[0099] In summary, adding soluble naphthoquinone small molecules or salt substances to the aqueous electrolyte can effectively weaken the Zn 2+ The solvation effect between water molecules is as follows: Figure 6 , 7 As shown. This additive enhances the stability of the metal electrode, reduces side reactions such as dendrite growth, surface passivation and hydrogen evolution corrosion, thereby protecting the zinc negative electrode and improving the stability of the hybrid capacitor. In particular, additives represented by MNQS, due to the interconversion between hydroxyl and aldehyde groups, exhibit good redox properties, promote charge transfer at the electrode-electrolyte interface, and realize additional conversion of electrical energy and chemical energy, increasing the specific capacity and energy density of the hybrid capacitor. The redox behavior of the electrolyte is based on the reversible conversion of "naphthoquinone-naphthol", in which H + Assists in the reduction of naphthoquinone, while OH - This method not only has a simple process and high cost-effectiveness, but also has a significant impact on improving the stability of hybrid capacitors and promoting their industrialization.

[0100] The above is a preferred embodiment of the present invention. It should be pointed out that a person skilled in the art can make several improvements and modifications without departing from the principle of the present invention. These improvements and modifications are also considered to be within the scope of protection of the present invention.

Claims

1. A hybrid electrolyte, characterized in that: It comprises naphthoquinone compounds, soluble zinc salts and water.

2. The hybrid electrolyte according to claim 1, characterized in that The concentration of the naphthoquinone compound in the hybrid electrolyte is 0.01-1000 mmol·L -1 .

3. The hybrid electrolyte according to claim 1, characterized in that The naphthoquinone compound is selected from substituted or unsubstituted 1,4-naphthoquinone, substituted or unsubstituted 1,2-naphthoquinone and corresponding salts or derivatives; The substituents of the substituted 1,4-naphthoquinone and the substituted 1,2-naphthoquinone are independently selected from hydroxyl, halogen, methyl, nitro and sulfonic acid groups.

4. The hybrid electrolyte according to claim 3, characterized in that The naphthoquinone compound includes at least one of 1,2-naphthoquinone, 1,2-naphthoquinone-4-sodium sulfonate, 1,4-naphthoquinone, 2,3-dichloro-5-nitro-1,4-naphthoquinone, 2-hydroxy-1,4-naphthoquinone, sodium bisulfite menadione, 2,3-dichloro-1,4-naphthoquinone, and 5,8-dihydroxy-1,4-naphthoquinone.

5. The hybrid electrolyte according to claim 1, characterized in that: The soluble zinc salt is at least one selected from zinc trifluoromethanesulfonate, zinc bistrifluoromethanesulfonate imide, zinc perchlorate, zinc sulfate, zinc chloride, zinc nitrate, zinc acetate, zinc fluoride, zinc hexafluoride, zinc tetrafluoroborate and zinc gluconate; And / or, the concentration of the soluble zinc salt in the hybrid electrolyte is 0.1-10 mol·L -1 .

6. The hybrid electrolyte according to claim 1, characterized in that The hybrid electrolyte also includes at least one of potassium salt, sodium salt, ammonium salt and nitrate.

7. The method for preparing the hybrid electrolyte according to any one of claims 1 to 6, characterized in that: The method comprises the following steps: mixing naphthoquinone compounds, soluble zinc salt and water to prepare a hybrid electrolyte.

8. Use of the hybrid electrolyte according to any one of claims 1 to 6 in the preparation of capacitors or batteries.

9. A hybrid capacitor, characterized in that: The hybrid electrolyte comprises a positive electrode, a negative electrode and any one of claims 1 to 6.

10. The hybrid capacitor according to claim 9, characterized in that: The positive electrode is a positive electrode current collector loaded with or without a positive electrode active material; the positive electrode active material is selected from at least one of activated carbon, carbon nanotubes, MXene, manganese-based oxides, vanadium-based oxides, Prussian blue derivatives, polyanion compounds, and organic positive electrode materials; And / or, the negative electrode is metallic zinc or a metal modified with metallic zinc.

Citation Information

Patent Citations

  • Three-dimensional 3-N heterocyclic naphthoquinone as well as preparation method and application thereof

    CN115873247A

  • Self-deoxidizing electrolyte additive of zinc metal battery, electrolyte and zinc metal battery

    CN116454419A

  • Application of aromatic micromolecule electrolyte additive

    CN116598606A

  • Application of benzoquinone micromolecules as additive in preparation of electrolyte

    CN117292952A